Ethnicity is not public service destiny: The political logic of service distribution in South Africa - John Porten; Inbok Rhee; Clark C. Gibson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Millions of South Africans in thousands of demonstrations have protested the unequal allocation of public services. Despite the African National Congress's promise to reduce the disparities generated by apartheid, the level of public services remains highly uneven across the country. Most studies of service provision in Africa assume that politicians will target their coethnics; other 'diversity deficit' literature hypothesizes that a high level of ethnic diversity undermines service provision from the start. Rather than assuming that ethnicity underlies service distribution in Africa, we argue that explanations of service provision should first examine how political institutions incentivize politicians to choose what services to distribute and how to distribute them. Even in an ethnicized polity, ethnic targeting may not be a politician's best strategy. We seek to explain the variation in service levels across South African municipalities and advance three hypotheses: (1) Municipal councillors in more ethnically diverse municipalities will form policy coalitions that produce higher service levels. (2) Due to their extensive powers and the possibility of being residual claimants to municipality resources, South African mayors will decrease services when they enjoy electoral safety. (3) The strategic interaction between councillors and their mayor helps to account for the variation in service provision across South Africa's municipalities. We test our hypotheses with data from more than 1.37 million households and aggregated municipality-level measures and find strong support for all three hypotheses. Political institutions-not ethnic demography-drive policy choices and service outcomes.
Keywords: D72; H41; O55; Z18; 330; public services; ethnicity; Africa; distributive politics; development policy; SouthAfrica